OTU-24 Appetite for improvement; 50% reduction in bloodstream infections in central venous catheter delivered parenteral nutrition. (June 2019) - Collins, Margaret; di Mambro, AJ
Abstract : Introduction: Bloodstream infection (BSI) is a recognised risk with parenteral nutrition (PN) administered via a central venous catheter (CVC) 1 . It can be life-threatening, leads to an extended hospital stay and, for patients reliant on PN, can mean –4 days without nutrition. NICE estimate the cost of each catheter-related BSI is £9, 900 2 . Methods: Quality improvement methodologies and tools were used to identify the problem, plan and test change ideas and measure improvements. BSI rates were recorded per 1000 days of PN to allow fair comparison of monthly BSI rates. The amount of PN administered per month was 8–16 days. A root cause analysis tool (RCA) was developed to investigate each BSI thought related to a CVC. RCA outcomes were reported to the relevant ward manager to highlight areas for improvement and guide action planning. Findings from the RCAs were plotted on a Pareto chart to identify the most frequently occurring factors on which to focus improvements. A driver diagram was used to plan the improvement process and identify change ideas. Engaging ward nurses, improving their knowledge and understanding of risk factors for developing a BSI and promoting best practice in management of CVCs were key aspects of this project. Actions: Pop-up ward based teaching for nursing staff to highlight the risk factors for BSI and clarify best practice for management of CVC and PN. Nurses completed an anonymous questionnaire to gauge knowledge of PN and care of a CVC. Their responses guided teaching topics and content of posters to highlight best practice in CVC care. Switch to single, rather than dual, lumen peripherally inserted central catheters (PICCs) to reduce the number of times the PICC was accessed. For in patients requiring PN for more than 28 days, we trialled the use of a protective cleaning cap on the CVC lumen3. Nutrition support team involvement in mandatory teaching sessions for F1 training and in Trust induction for safe CVC access in PN patients were also implemented. Results: A 50% reduction in BSI rates in 2018 compared to 2017. Conclusions: RCA findings show that a number of factors contributed to our patients developing a BSI. Various strategies were used to improve BSI rates. The use of quality improvement tools and methodologies in all stages of this project was key to its success. Future work develop a PN e-learning module ward-based CVC update training This quality improvement project has focused on BSI in patients receiving PN however it could be applied to improving the care and use of all CVCs in our Trust. (1) Pironi L, Arends J, Bozzetti F, Cuerda C, Gillanders L, Jeppesen PB, Jolly F, Kelly D, Lal S, Staun M, Szczepanek K, Van Gossum A, Wanten G, Schneider SM, ESPEN Guidelines on chronic intestinal failure in adults. Clinical Nutrition . 2016;35(2): 24–07. (2) NICE. The 3M Tegaderm CHG IV securement dressing for central venous and arterial catheter insertion sites . Available from: https://www.nice.org.uk/guidance/mtg25/chapter/5-Cost-considerations [Accessed 13th February 2019]. (3) NICE. Curos disinfecting cap for needleless connectors . Available from: https://www.nice.org.uk/advice/mib143/chapter/The-technology [Accessed 13th February 2019].